KINERJA DINAS KOPERASI DAN UMKM - Meyzi Heriyanto, Syahirul Alim, Zaili Rusli, (Jurnal Ilmu Administrasi Negara, 2019)
Performance of Cooperative and UMKM Offices. This study aims to analyze how much the performance of the Employees of the Pekanbaru City Cooperative and SMEs Office in fostering cooperatives in the administrative area of Pekanbaru Municipality. This research is qualitative. Data collection was carried out by library research and field research using observations and interviews. The data will then be analyzed qualitatively. With a population of 40 people used as respondents. The research informants were the Lurah, the Head of the Office, LKMD and RW. Based on the results of research conducted, it can be concluded that employee performance is influenced by individual factors related to the background and experience of employees, psychological factors that include employee attitudes towards cooperative problems that exist and organizational factors that awaken the hierarchical system of the service so that there is awareness in the main tasks and the function of each field The performance of the UMKM Cooperative Office in Pekanbaru City in 2014 had a positive impact on the development of cooperatives in Pekanbaru City. The State Civil Society must be aware of their duties and roles in public service to the community in the field of Cooperatives and MSMEs in Pekanbaru City so that employee performance will increase the growth of cooperatives and new entrepreneurs is increasing rapidly.